Tingkat Kepuasan Wisatawan Terhadap Kualitas Pelayanan Di Sanggar Seni Yasa Putra Sedana di Kecamatan Payangan, Kabupaten Gianyar, Bali - Ardita, I Kadek; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2019)
Yasa Putra Sedana is an art studio engaged in dance and percussion, In its activities, Yasa Putra Sedana must be able to compensate with good service to tourists so that tourists feel happy and comfortable. This study aims to analyze the level of tourist satisfaction with the quality of services provided by employee, in order to determine the level of satisfaction of tourists who come to the Yasa Putra Sedana Art Studio and then can be further evaluated. This research was conducted at the Yasa Putra Sedana Art Studio in Banjar Pengaji, Melinggih Kelod Village, the District of Payangan, Gianyar Regency, Bali Province, the type of data in this study used quantitative and qualitative data, where the data were obtained using a questionnaire distribution method, in-depth interviews, observations / Observation and documentation. The sampling technique used in this research is purposive sampling technique, and then the data obtained were analyzed with a qualitative descriptive technique using a Likert scale. The results of this research is, that the level of tourist satisfaction with the quality of service at the Yasa Putra Sedana Art Studio gets a very satisfied value, this is obtained from the results of the calculation of the average score obtained from the distribution of questionnaires from the level of performance and level of importance to all the indicators that affect the level tourist satisfaction, obtained a yield of 101.189% (very satisfied). Keywords: Tourist Satisfaction Level, Service Quality, Studio Art.